Dysregulation in the microbiota by HBV and HCV infection induces an altered cytokine profile in the pathobiome of infection - Marcos Daniel Mendes Padilha; Francisco Tiago de Vasconcelos Melo; Rogério Valois Laurentino; Andrea Nazaré Monteiro Rangel da Silva; Rosimar Neris Martins Feitosa (Brazilian Journal of Infectious Diseases)
Viral hepatitis is a public health problem, about 1 million people die due to complications of this viral disease, the etiological agents responsible for inducing cirrhosis and cellular hepatocarcinoma are HBV and HCV, both hepatotropic viruses that cause asymptomatic infection in most cases. The regulation of the microbiota performs many physiological functions, which can induce normal intestinal function and produce essential nutrients for the human body. Metabolites derived from gut microbiota or direct regulation of host immunity and metabolism have been reported to profoundly affect tumorigenesis in liver disease. If the microbiota is unbalanced, both exogenous and symbiotic microorganisms can affect a pathological process. It is well understood that the microbiota plays a role in viral diseases and infections, specifically the hepatic portal pathway has been linked to the gut-liver axis. In HBV and HCV infections, the altered bacterial representatives undergo a state of dysbiosis, with subsequent establishment of the pathobiome with overexpression of taxons such as Bacteroides, Clostridium, Lactobacillus, Enterobacter, and Enterococcus. This dysregulated microbiome induces a microenvironment conducive to the development of hepatic complications in patients with acute and chronic HBV and HCV infection, with subsequent dysregulation of cytokines IFN-α/β, TNF-α, IL-1β, TGF-β, IL-6 and IL-10, which alter the dysfunction and damage of the hepatic portal system. In view of the above, this review aimed to correlate the pathophysiological mechanisms in HBV and HCV infection, the dysregulation of the microbiome in patients infected with HBV and HCV, the most altered cytokines in the microbiome, and the most altered bacterial representatives in the pathobiome of infection.